Educação lúdica: uma mediação ao processo de desenvolvimento infantil - Basso, Berenice Geschwind (2002)
Playful Education: a mediation to the process of infantile development, is a study had on the theories that currently have unmasked and identified the interactions of the educative process as principle of mediation between the citizens that if relate and change experiences, in infancy, giving felt human to the practised shares. The boarding of the concepts on playing, trick and game is visualized as elements of essential bedding for the organization of the directed educational projects to the infantile education. The gotten results and the application of relative instruments to " playing of... " had supplied to conjugated knowledge of abilities and attitudes of children who englobaram its to know in the related expressions the values, religiosidade, aesthetic ethics and, hierarchy, power, sexuality and preconception, through the references and customs in the papers that had assumed during the carried through meeting. The human direction of the practised shares had been express for the attitudes related to the work, education, solidarity, care, fear, protection, health, feeding, shelter, family and confraternização. All these situations had been recorded, leaving filed an important document on the daily one of the infantile school.